New method for community detection in social networks extracted from the Web - Ganjaliyev, Fadai (2012 IV International Conference Problems of Cybernetics and Informatics, 2012)
Social networks have attracted much attention recently. Social network analysis finds its application in many current business areas. Different studies have been conducted to automatically extract social networks among various kinds of entities from the Web. Community detection is one of the most important and interesting research areas in social network analysis. Many works are dedicated to methods and algorithms for detecting communities in different kinds of social networks extracted on the Web. Below we give a brief description of a new method which can help to identify communities in networks.